Analysis of the Role of Government Internal Supervisory Apparatus (APIP) in the Prevention and Detection of BOS Fund Fraud (Case Study of the Regional Inspectorate of North Sulawesi Province) - Febriantini, A. Aulia; Warongan, Jessy D.L; Datu, Christian (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this research is to understand how APIP performs its role in preventing and detecting fraud in BOS funds. The research method used is a qualitative approach with a case study method. The research findings indicate that the role of APIP at the North Sulawesi Regional Inspectorate in overseeing BOS funds is in accordance with existing regulations, through audit examinations of high schools, vocational schools, and special needs schools (SMA/SMK/SLB) that receive the funds. APIP also conducts reviews, monitoring, and evaluation of the follow-up actions from the audit examinations to detect and prevent fraud in the management of BOS funds. However, there are challenges in supervising BOS funds, including budget constraints, limited time, human resources, facilities, and inadequate conditions.